2021
DOI: 10.1108/itse-08-2020-0128
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning during COVID-19 pandemic: satisfaction, opportunities and challenges as perceived by faculty members and students

Abstract: Purpose This study aims to investigate and assess the first experience of faculty members and students with distance learning implemented at Al Ain University (AAU) to contain the spread of Coronavirus or COVID-19. The paper attempted to understand faculty and students’ satisfaction with institutional readiness for distance learning and perception towards opportunities and challenges of distance learning. Design/methodology/approach The study is based on data collected in March 2020 through an online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 40 publications
2
52
0
3
Order By: Relevance
“…One way to circumvent this challenge is to draw upon an existing conceptual framework related to the problem and use it to inform the design of the instrument (e.g. Hattingh et al 2020;Jeffery and Bauer 2020;Refae, Kaba, and Eletter 2021). Another is to use or adapt an existing instrument (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One way to circumvent this challenge is to draw upon an existing conceptual framework related to the problem and use it to inform the design of the instrument (e.g. Hattingh et al 2020;Jeffery and Bauer 2020;Refae, Kaba, and Eletter 2021). Another is to use or adapt an existing instrument (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Distance learning technologies include: case technologies; TV technologies; network technologies. The means of distance education are technical (computers, global and local networks) and software (relational databases, computer training programs, computer electronic textbooks, knowledge test control programs) (El Refae et al, 2021).…”
Section: The Essence Of Distance Education Of Future Managers Of Physical Culture and Sports Under The Influence Of Post-pandemic Consequmentioning
confidence: 99%
“…Teaching Mathematics via online was very challenging as students are accustomed to the method of F2F learning since early education (El Refae et al, 2021;Nugroho et al, 2021). It found that students were commonly less proficient in spelling and mathematical calculations skills compared to reading skills (Kuhfeld et al, 2020;Pavlovic et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Chukwuemeka et al, 2021;Okoye et al, 2021). Besides, students must had additional efforts such as watching online lectures on YouTube or purchase optional remote learning sources such as question banks (El Refae et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%